Mammalian Brain Development - Janigro, Damir (Contemporary Neuroscience, 2009)
This book charts the way forward through the field of mammalian brain development, in which the integration of biological function can occur at all levels between the gene and the organism itself. Mammalian Brain Development examines the traditional "nature versus nurture" argument in the spectrum of brain development, discussing in particular sex differences in spatial perception ability, phenotype plasticity, disorders of brain development, Blood-Brain and placental barriers, chromosome abnormalities, as well as the use of imaging techniques. Geared toward neuroscientists, neurologists, pediatricians, pediatric psychiatrists, and neuroimmunologists, this volume paves the way toward the realization that the development of an individual is fundamentally an interaction between its genes and environment.